Pengaruh DER, ROA, ROE, NPM, dan Risiko Sistematis pada Harga Saham Perusahaan - Nia Damayanti; Etty Gurendrawati; Santi Susanti (Jurnal Simki Economic, 2023)
This study aims to analyze the effect of Debt to Equity Ratio, Return on Assets, Return on Equity, Net Profit Margin, and Systematic Risk on companies that are members of the LQ45 Index listed on the IDX for the 2017-2019 period. Secondary data used in this research is the annual report and company financial statements, with quantitative research methods. The technique used in the selection of the sample is purposive sampling, where from 62 companies that are members of the LQ45 Index, 30 companies are obtained that meet the sample criteria. The data were analyzed using descriptive statistical analysis, estimation model selection test, classical assumption test, panel data regression analysis, and hypothesis testing. The results of this study indicate that Return on Equity and Systematic Risk have a significant effect on stock prices and Debt to Equity Ratio, Return on Assets, and Net Profit Margin have no significant effect on stock prices.